2019
DOI: 10.1007/s11192-019-03205-w
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of simulation models of peer review

Abstract: Peer review is a process used in the selection of manuscripts for journal publication and proposals for research grant funding. Though widely used, peer review is not without flaws and critics. Performing large-scale experiments to evaluate and test correctives and alternatives is difficult, if not impossible. Thus, many researchers have turned to simulation studies to overcome these difficulties. In the last 10 years this field of research has grown significantly but with only limited attempts to integrate di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…Comparative empirical research across systems has been especially difficult. Simulation research on peer review has been a promising approach where the lack of empirical data is hindering progress (Roebber, & Schultz, 2011;Feliciani, Luo, et al, 2019). Automated methods for supporting journal peer review have been suggested as far back as the 1980s (Garfield, 1987).…”
Section: Author Contributionsmentioning
confidence: 99%
“…Comparative empirical research across systems has been especially difficult. Simulation research on peer review has been a promising approach where the lack of empirical data is hindering progress (Roebber, & Schultz, 2011;Feliciani, Luo, et al, 2019). Automated methods for supporting journal peer review have been suggested as far back as the 1980s (Garfield, 1987).…”
Section: Author Contributionsmentioning
confidence: 99%
“…Murray et al (2019) examined whether peer review outcomes at a biosciences journal are influenced by author-referee homophily (i.e., the preference of referees for manuscripts from authors with shared -10 -characteristics) and found evidence for higher rates of acceptance in the case of gender and country homophily. In a scoping review, Feliciani et al (2019) identified 46 studies that represented elements of peer review in computational models (e.g., agent-based models, latent Markov models). Computational models are thus likely the most common approach so far to theorize peer review.…”
Section: Some Theoretical Efforts On Peer Reviewmentioning
confidence: 99%
“…The Committee on Publication Ethics (COPE) asserts that peer-review in all its forms plays a pivotal role in ensuring the integrity and liability of scholarly records (1), which leads to a higher quality of research. However, several criticisms of the peer-review process exist (2).…”
Section: Introductionmentioning
confidence: 99%
“…The current knowledge dissemination model is characterized by the presentation of research ndings which go through the inspection of journals that de ne priority themes, formats, and speci c evidence. In this regard, journals are able to decide what is published, by whom, when, and how (2,5,6). Because of this structure, such a model does not encourage controversy or public debate.…”
Section: Introductionmentioning
confidence: 99%